THE EFFECT OF PERCEPTIONS OF EASE OF USE AND PERCEPTIONS OF USEFULNESS ON INTEREST IN MEDIATION BY ATTITUDES OF USERS OF BRI INTERNET BANKING SERVICES IN THE SPECIAL AREA OF YOGYAKARTA - M. Alifio Fahmi Rosyidin; Dyah Sugandhini; Sri Harjanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the effect of perceived ease of use and perceived usefulness on interest mediated by the attitudes of BRI internet banking service users in DI Yogyakarta. researchers used a quantitative approach to the survey method. The population in the study were all BRI internet banking service users in the Special Region of Yogyakarta. The number of samples used was 180 respondents, determined through purposive sampling technique. The data analysis tool uses Partial Least Square (PLS) based Structural Equation Modeling (SEM). The results showed that perceived ease of use and perceived usefulness directly had a positive and significant effect on the attitudes of BRI internet banking users in DI Yogyakarta. Perceived ease of use and perceived usefulness directly have a positive but not significant effect on interest in BRI internet banking users in the Special Region of Yogyakarta. Attitudes directly have a positive and significant effect on interest in BRI internet banking users in the Special Region of Yogyakarta. Perceived ease of use and perceived usefulness indirectly have a positive and significant effect on interest mediated by attitudes towards BRI internet banking users in the Special Region of Yogyakarta Keyword: Perceived ease of use, Perceived Usefulness, Attitudes, Interest, Internet Bank